2016
DOI: 10.1055/s-0036-1586161
|View full text |Cite
|
Sign up to set email alerts
|

Mature Cystic Teratoma of Ovary with Abnormally High Levels of Ca19-9: A Case Report

Abstract: Mature cystic teratomas, or dermoid tumors, are the most common benign ovarian neoplasms in young women. Malignant transformation is rare, and occurs in less than 2% of the cases. The heterogeneous histological composition of these tumors may be responsible for the occasional elevation of various tumor markers, such as Ca19?9 and Ca125. We describe one case of mature cystic teratoma in a 50-year old woman with the second highest level of Ca19?9 (8922.76 UI/mL) described in the literature. We concluded that abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Pyeon et al [5] reported a case of a benign ovarian cyst with CA 19-9 levels of 2,753 U/mL that then returned to normal postoperatively [5]. Similarly, Sampaio et al [4] reported an MCT in a 50-year-old woman with the second highest reported level of CA 19-9 (8922.75 U/mL) [4]. These findings have led to more comprehensive research.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Pyeon et al [5] reported a case of a benign ovarian cyst with CA 19-9 levels of 2,753 U/mL that then returned to normal postoperatively [5]. Similarly, Sampaio et al [4] reported an MCT in a 50-year-old woman with the second highest reported level of CA 19-9 (8922.75 U/mL) [4]. These findings have led to more comprehensive research.…”
Section: Discussionmentioning
confidence: 98%
“…We present this case in order to build on the growing body of evidence suggesting that CA 19-9 levels are useful in the diagnosis and management of MCT [7,10]. Cases of ovarian neoplasms such as ovarian clear-cell and endometrioid carcinomas [11] with increased CA 19-9 levels, and benign neoplasms with increased CA 19-9 have been documented in the literature previously [3][4][5]. Pyeon et al [5] reported a case of a benign ovarian cyst with CA 19-9 levels of 2,753 U/mL that then returned to normal postoperatively [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we report six cases of patients with AIP, causing the elevation of CA 19-9 ranging from 1950 U/mL to 12,000 U/mL, and a case of a patient with liver steatosis and an increased CA 19-9 value to 1930 U/mL. When considering differential diagnosis due to the low specificity of tumor markers and lack of obvious radiological image, various diseases should be taken into consideration [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 68 , 69 ]; however, a mildly increased dimension of the pancreas in MRI with areas of fluid signals could correspond to past AIP that induced increased CA 19-9. According to the literature, about 25% of patients with AIP show values of CA 19-9 > 37 U/mL, and only around 12.2% of them show elevated levels > 100 U/mL [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a tumor marker, CA 19-9 had a relationship with anxiety in our study. Also, a case report concluded that a high level of CA 19-9 is not necessarily associated with ovarian malignancy and may be due to patients' anxiety (34). Overall, tumor markers such as CA 125 and CA 19-9 can elevate in various non-malignant processes, including liver diseases.…”
Section: Discussionmentioning
confidence: 99%